2016
DOI: 10.4137/bbi.s38192
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Synonymous Codon Usage in the Mitogenomes of Certain Species of Bilaterian Lineage with Special Reference to Chaetognatha

Abstract: Chaetognatha is a minor phylum, comprising transparent marine invertebrates varying in size from 0.5 to 12 cm. The exact phylogenetic position of Chaetognatha in Metazoa has not been deciphered as some embryological characteristics place chaetognaths among deuterostomes and some morphological characteristics place these among protostomes. In this study, the major factors that drive synonymous codon usage bias (SCUB) in the mitogenomes of representative species of Chaetognatha and chosen species of other closel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The existence of positive correlations between homogeneous nucleotide contents and negative correlations between heterogeneous nucleotide contents implies that mutational pressure due to compositional constraints might play a crucial role in shaping the codon usage. 64 In the case of viral genomes, the positively correlated heterogeneous contents and the negatively correlated homogeneous contents indicate natural selection by the host. 24 In this study, significant positive correlations were found between A and A 3 , T and T 3 , G and G 3 , and C and C 3 .…”
Section: Resultsmentioning
confidence: 99%
“…The existence of positive correlations between homogeneous nucleotide contents and negative correlations between heterogeneous nucleotide contents implies that mutational pressure due to compositional constraints might play a crucial role in shaping the codon usage. 64 In the case of viral genomes, the positively correlated heterogeneous contents and the negatively correlated homogeneous contents indicate natural selection by the host. 24 In this study, significant positive correlations were found between A and A 3 , T and T 3 , G and G 3 , and C and C 3 .…”
Section: Resultsmentioning
confidence: 99%
“…In this study, patterns of SCUB and various factors which influence the formation of SCUB patterns in selected individuals of MCV-1 and MCV-2 were examined in detail. Positively correlated homogeneous base contents and negatively correlated heterogeneous base contents in MCV-1 and MCV-2 indicate the major influence of mutational pressure [66]. However, correlation analyses revealed the existence of positive heterogenous correlations (T and A3; C and G3) in all selected MC viruses.…”
Section: Discussionmentioning
confidence: 86%